Analisa Kualitas Tidur Terhadap Kontrol Gula Darah Pada Penderita Diabetes Melitus: Systematic Review - Mataputun, Donny Richard; Rimbun, Lenny Rosbi; Rahayu, Cicielia Ernawati (NHM PRESS, 2023)
The abstract should summarize the content of the paper. Try to keep the abstract below 200 words. Do not make references nor display equations in the abstract. The journal will be printed from the same-sized copy prepared by you. Your manuscript should be printed on A4 paper (21.0 cm x 29.7 cm). It is imperative that the margins and style described below be adhered to carefully. This will enable us to keep uniformity in the final printed copies of the Journal. Please keep in mind that the manuscript you prepare will be photographed and printed as it is received. Readability of copy is of paramount importance.